Age-Related Changes in Dynamic Postural Control and Attentional Demands are Minimally Affected by Local Muscle Fatigue - Remaud, Anthony; Thuong-Cong, Cécile; Bilodeau, Martin (Frontiers in Aging Neuroscience, 2016)
Normal aging results in alterations in the visual, vestibular and somtaosensory systems, which in turn modify the control of balance. Muscle fatigue may exacerbate these age-related changes in sensory and motor functions, and also increase the attentional demands associated with dynamic postural control. The purpose of this study was to investigate the effect of aging on dynamic postural control and posture-related attentional demands before and after a plantar flexor fatigue protocol. Participants (young adults: n=15; healthy seniors: n=13) performed a dynamic postural task along the antero-posterior and the medio-lateral axes, with and without the addition of a simple reaction time task. The dynamic postural task consisted in following a moving circle on a computer screen with the representation of the center of pressure (COP). This protocol was repeated before and after a fatigue task where ankle plantarflexor muscles were targeted. The mean COP-target distance and the mean COP velocity were calculated for each trial. Cross-correlation analyses between the COP and target displacements were also performed. Reaction times were recorded during dual-task trials. Results showed that while young adults adopted an anticipatory control mode to move their COP as close as possible to the target center, seniors adopted a reactive control mode, lagging behind the target center. This resulted in longer COP-target distance and higher COP velocity in the latter group. Concurrently, reaction time increased more in seniors when switching from static stance to dynamic postural conditions, suggesting potential alterations in the central nervous system functions. Finally, plantar flexor muscle fatigue and dual-tasking had only minor effects on dynamic postural control of both young adults and seniors. Future studies should investigate why the fatigue-induced changes in quiet standing postural control do not seem to transfer to dynamic balance tasks.